Reducing of CO2 emissions and its depositing into underground - Jaroslava Koudelková; Pavel Prokop (Acta Montanistica Slovaca, 2005)
Increasing CO2 emissions caused especially by the combustion of fossil fuels rises a question of how this can be problem solved in the long term. There is several solutions which differ technically and financially. This paper deals with the CO2 capture from combustion processes or power plant processes, (CO2 can be captured from the flue gas, after combustion in oxygen and recirculated flue gas or from a synthesis gas before combustion). This paper presents possibilities of CO2 storagex captured in this way into underground (deep ocean, oil and gas fields, coal bed, aquifers).